Hydration Mechanisms of Gelled Paste Backfills for Potash Mines Using Lime as a Gel Material - Rongzhen Jin; Xue Wang; Xuming Ma; Huimin Huo; Siqi Zhang; Jiajie Li; Wen Ni (Gels, 2024)
This paper investigates the flow performance and mechanical properties of underground gelled filling materials made from potash mine tailings, using lime as a gel. It demonstrates the feasibility of using lime as a gel, potash mine tailings as aggregate, and replacing water with potash mine tailings to create filling materials that meet design requirements for flow and compressive strength. The role of lime in the hardening process is explored through X-ray diffraction, scanning electron microscopy with energy-dispersive X-ray spectroscopy, thermogravimetric analysis, and infrared analysis. Results show that hydration products vary with lime dosage. With 9% lime (L9), the products are primarily ghiaraite (CaCl2·4H2O) and carnallite (KMgCl3·6H2O); with 5% lime (L5), tachyhydrite (CaMg2Cl6·12H2O) predominates, along with minor amounts of antarcticite (CaCl2·6H2O) and korshunovskite (Mg2Cl(OH)3·4H2O); and with 2.6% lime (L2.6), the products include tachyhydrite, ghiaraite, bischofite (MgCl2·6H2O), and korshunovskite. These hydration products form a dense, interwoven structure, enhancing the strength of the filling material. This study offers a theoretical foundation for using lime gel as a filling material in potash mining, with significant implications for sustainable mining practices.